PERAN ULAMA PEREMPUAN DALAM MEMELIHARA BUDAYA ORGANISASI DI PESANTREN - Sadiyah, Halimatus (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Female Ulama are different from female scholars. If female ulama are female scholars, then female ulama are ulama (both women and men) who have a gender perspective. The meaning of women has shifted not only biologically, but also ideologically. The existence of the pesantren is influenced by the values, perceptions, policies, habits and behavior of the people in it. Has characteristics that can influence the formation of positive attitudes and morals. Women clerics, or so-called bu Nyai in Javanese terms, are culture creators who play an important role in the pesantren. The role of organizational leaders in maintaining organizational culture, with a concentration on the issue of eliminating violence against women, preventing child marriage, extremism and environmental fatwas. The role of female ulam can be seen when determining boundaries, meaning that they are able to create clear cultural differences between one organization and another. Second, it plays a role in facilitating and generating organizational commitment above individual interests. Third, the role of bringing a sense of identity to organizational members. Fourth, plays a role in the stability of the social system.